The Role of e-Leadership, Career Development and Loyalty on Employee Performance - Joko Tri Brata; Abdul Nashar; Suyuti HM; La Ode Abdul Manan (International Journal of Artificial Intelligence Research, 2022)
Objective in study this is for know influence virtual leadership against loyalty employees, development career to loyalty employees, virtual leadership towards performance employees, development self to performance employees and loyalty employee to performance employees. Study this including type study quantitative, Subject taken in study this are 380 employees in Indonesia public organizations. with random sampling system method. Data obtained with spread online questionnaire with scale Likert 1 to with 7 via social media, analysis technique using Structural Equation Modeling (SEM) with tool help data processing software SmartPLS 3.0. Independent variable in study this are virtual leadership, career development and loyalty while the dependent variable is employee performance. Conclusion in study this Influential virtual leadership to loyalty employees, Development career influential to loyalty employees, Influential virtual leadership to performance employees. Development Career influential to performance employees. Loyalty employee influential to performance employees.